Evolution of Microcontroller-based Remote Monitoring System Applications - Wael A. Salah; Basem Abu Zneid (Institute of Advanced Engineering and Science, 2019)
This study reviews the evolution of smart applications of microcontroller-based wireless/wired remote monitoring systems. Rapid developments in science and technology offer the advantages of using integrated embedded chips, microprocessors, and microcontrollers. The use of microcontrollers in industrial processes, such as automobiles, aeronautics, space, robotics, electronics, defense applications, mobile communications, rail transport, and medical applications, is rapidly increasing. This study aims to review the progress of microcomputers in smart remote monitoring and controlling applications for the control and management of different systems using wireless/wired techniques